2009
DOI: 10.5551/jat.no1347
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary n-6/n-3 PUFA Ratio Promotes HDL Cholesterol Level, but does not Suppress Atherogenesis in Apolipoprotein E-Null Mice 1

Abstract: Aim: Dietary fatty acids affect atherogenesis, which was presumed to be partly related to HDL cholesterol (HDL-C) metabolism. The major aim of the work was to analyze various ratios of n-6 / n-3 PUFA diets on HDL-C metabolism in apolipoprotein E-null (apoE / ) mice, which have similar symptoms to human type familial hyperlipoproteinemia. Methods: Two-month-old male apoE / mice were fed four types of n-6 / n-3 PUFA diet (group 1, 1.28; group 2, 5.03; group 3, 9.98 and group 4, 68.26) and control diet, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
1
16
2
Order By: Relevance
“…The activity of LPL was highest in the group whose dietary ω-6/ω-3 PUFA ratio was the lowest (3:1), and our results showed that this ratio improved the absorption of TG in the body. However, the results of the present study were different from those of a previous study (Zhang et al, 2009), where dietary n-6:n-3 PUFA ratios were 1.28, 5.03, 9.98, 68.62, which showed that the different n-6:n-3 PUFA ratios had no effect on the expression of LPL in the mouse liver. This might due to difference in the species and the different n-6:n-3 PUFA ratios.…”
Section: Discussioncontrasting
confidence: 99%
“…The activity of LPL was highest in the group whose dietary ω-6/ω-3 PUFA ratio was the lowest (3:1), and our results showed that this ratio improved the absorption of TG in the body. However, the results of the present study were different from those of a previous study (Zhang et al, 2009), where dietary n-6:n-3 PUFA ratios were 1.28, 5.03, 9.98, 68.62, which showed that the different n-6:n-3 PUFA ratios had no effect on the expression of LPL in the mouse liver. This might due to difference in the species and the different n-6:n-3 PUFA ratios.…”
Section: Discussioncontrasting
confidence: 99%
“…However, concerns have been raised regarding high n-6 intake may accelerate the conversion of n-6 18: 2 LA into 20:4 AA, which is a major substrate of pro-inflammatory eicosanoids and cytokines. Although there are inconsistent findings of protective effects of n-3 FA on atherogenesis in animal models 30, 42 , lower ratios of n-6/n-3 FA intakes are still favorable toward reducing atherosclerosis 43, 44 . Might our results be related to the effects of the different diets on n-6 FA intake?…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that the efficacy of n-3 PUFAs in protection against atherosclerosis depends not only on the amount of n-3 PUFAs but also on the background level of n-6 PUFAs. 23 Recent findings 20,24,25 suggest that a low ratio of n-6/n-3 fatty acids (close to 1:1) is desirable in reducing the risk of many chronic diseases that are highly prevalent in Western societies, including atherosclerotic cardiovascular disease and inflammatory diseases. However, the role of the n-6/n-3 fatty acid ratio in the development of atherosclerosis remains to be established in well-qualified in vivo models.…”
Section: See Accompanying Article On Page 2325mentioning
confidence: 99%